V.1 (England, 1993)
Excerpt from the Introduction: Public choice - or the economics of politics - is a relatively new science located at the interface between economics and politics, founded in 1948 by Duncan Black, who died in 1991 without ever achieving full recognition as the Founding Father of the discipline. Its practitioners seek to understand and to predict the behaviour of political markets by utilizing the analytical techniques of economics, most notably the rational choice postulate, in the modelling of non-market decision-making behaviour. Public choice, thus defined, is a positive science concerned with what is or what conditionally might be. Its normative counterpart, concerned with what should be, is social choice, the subject-matter of separate volumes.
Keywords: Social choice